Pelatihan Teknologi Budidaya Udang Sistem Polikultur pada Kelompok Tani Pembudidaya Udang Di Desa Tamarupa Kecamatan Mandalle Kabupaten Pangkep, Provinsi Sulawesi Selatan - Harlina, Harlina; Saenong, Muhammad; Hamdillah, Andi (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
One of the villages in Pangkajene and Islands District is Tamarupa Village, Mandalle District, which is a coastal area. Most of the population are fish farmers. In this village, there is a shrimp farmer group "Sipakaenre II". The main problem faced by farmer group is the low production of shrimp because the technology used is still traditional, relying on natural food and using the monoculture method. Shrimp production can be increased by improving aquaculture technology. For this reason, the purpose of this community partnership program (CPP) was to provide a better understanding and skill to shrimp farmer groups about how to cultivate good shrimp through training activities of polyculture shrimp farming techniques based on Best Aquaculture Practice (BAP). The approach method used to achieve the objectives of the community partnership program was a participatory method. After this activity, there was an increase in the knowledge and skills of farmer group partners about shrimp aquaculture technology with BAP-based on polyculture systems.